The effects of body image impairment on the quality of life of non-operated Portuguese female IBD patients - Trindade, Inês A. (2016)
Objectives: Inflammatory bowel diseases (IBD) and their treatment are known to negatively impact on patients’ body image, especially female patients. However, although there are broad evidences of body image impairment in female IBD patients, its negative impact on the quality of life (QoL) of non-operated women is not clearly and specifically studied. The aim of the current study was therefore to analyse, in a sample of non-operated female IBD patients, the factors that contribute to body image impairment and its impact on QoL. Methods: Ninety-six non-operated women (39.7 % with CD and 60.3 % with UC), aged between 18 and 40 years old, completed an online survey with validated self-report measures, which included the Body Image Scale and the WHO Brief Quality of Life Assessment Scale. Results: Negative body image was correlated with lower psychological and physical QoL and increased corticosteroids use, associated medical complications, body mass index (BMI), and IBD symptomatology. Regression analyses revealed that BMI and IBD symptomatology significantly predicted body image impairment. Furthermore, results from path analyses indicated that BMI and IBD symptomatology’s effect on psychological and physical QoL was mediated through the negative effects of body image impairment. This model explained 31 % of psychological QoL and 41 % of physical QoL. Conclusions: These findings suggest that non-operated female patients are subject to pervasive and harmful effects of body image impairment on psychological and physical functioning. Therefore, psychological interventions aiming to target body dissatisfaction should be implemented in the health care of IBD, independently of patients’ operative status.